Does HMB enhance body composition in athletes? A systematic review and meta-analysis - Holland, B. M.; Roberts, B. M.; Krieger, J. W.; Schoenfeld, B. J. (The Journal of Strength and Conditioning Research, 2022)
The purpose of this article was to systematically review and meta-analyze the current literature to determine the effects of HMB on body composition in athletes. Studies were deemed eligible for inclusion if they met the following criteria: (a) were an experimental design published in a peer-reviewed, English-language journal; (b) included human athletic populations; (c) assessed body mass (BM), fat mass (FM), or fat-free mass (FFM) using a validated measure; (d) and had a minimum supplementation period of 4 weeks. Separate analyses were performed for BM, FM, and FFM using robust variance random-effects meta-regression for multilevel data structures, with adjustments for small samples. The final analysis of BM comprised a total of 208 subjects from 7 studies. Analysis of FFM and FM encompassed 5 studies comprising 161 subjects and 5 studies comprising 128 subjects, respectively. The principal finding of this analysis suggests HMB may have a small, positive impact on FFM in athletes (0.30 ± 0.13; 95% confidence interval [CI]: -0.07 to 0.68; p = 0.08), although this seems specific to when protein intake is suboptimal (<1.6 g·kg-1·d-1). Consistent with previous research on athletes, HMB demonstrated no significant effect on BM (-0.02 ± 0.04; 95% CI: -0.14 to 0.10; p = 0.70) and a small, nonsignificant effect on FM (-0.33 ± 0.23; 95% CI: -0.96 to 0.31; p = 0.22). More research is required to establish HMB's influence on FFM in athletes. It is also important to consider the dosage of HMB and training parameters of athletes because these will likely influence the efficacy of supplementation.